Impact of Mouse Strain on Arrested Alveolarization in Response to Hyperoxia Exposure as Neonates - Tiono, Jennifer; Justus Liebig University Giessen (My University, 2023)
Bronchopulmonary dysplasia (BPD) is a common complication of preterm birth that can cause significant morbidity and mortality in neonates. Despite identifying several risk factors and causes, the exact pathogenesis of BPD remains unclear, and further research is needed to understand it. Animal models are commonly used to study BPD to simulate the condition and test different stimuli, but the use of various mouse strains can sometimes yield conflicting results. Several reports suggest that the mouse strain used in experimental studies is a critical factor that can impact the results and data obtained and should therefore be carefully considered during experiment design and interpretation. As a result, there is a pressing need for a comparative analysis of lung alveolarization and the gene expression of critical mediators of the lung antioxidant response in various commonly used mouse strains. By conducting such analyses, researchers can make informed decisions on the most appropriate mouse strain to employ in BPD studies. To this end, this study conducted a comprehensive comparison of lung alveolarization and the gene expression of key mediators of the lung antioxidant response in six commonly used inbred mouse strains (C57BL/6J, BALB/cJ, FVB/NJ, C3H/HeJ, DBA/2J and 129S2/SvPasOrlRj). The mice were exposed to normoxic or hyperoxic conditions for the first 14 days of postnatal life. Lung perturbation was evaluated using design-based stereology. Gene expression of the lung antioxidant response was assessed using real-time reverse transcriptase polymerase chain reaction and immunoblot. The study revealed that hyperoxia caused varying degrees of changes in lung architecture in all five mouse strains, with the C57BL/6J strain being the most sensitive to hyperoxia. The C57BL/6J strain showed the most significant changes in terms of alveoli number, alveoli density, mean linear intercept (MLI), and lung volume. In contrast, the FVB/NJ strain demonstrated the most significant increase in septal thickness following exposure to hyperoxia, while the C57BL/6J strain was the least affected in this aspect. Additionally, the C3H/cj strain showed the smallest degree of change in terms of alveolar density and mean linear intercept (MLI). Additionally, the gene expression of key mediators of the lung antioxidant response exhibited variations among the different strains, indicating a strain-dependent influence. The C57BL/6J strain showed the most significant alterations in gene expression, with a notable upregulation of a wide range of antioxidants such as SOD1, SOD2, SOD3, GSS, GPX, PON2, TXNRD2, and PRDX6 compared to the other strains. Baseline gene expression also differed among the strains under normoxic and hyperoxic conditions. In conclusion, this study shows that the mouse genetic background significantly affects the outcome of lung development under the influence of hyperoxia.
Keywords: ddc:610